PEMILIHAN KEPALA DAERAH MELALUI DPRD DALAM SISTEM KETATANEGARAAN INDONESIA - Micze Ridua, Srye (Honeste Vivere, 2025)
The discourse of returning the regional head election system from direct election by the people to election through the DPRD has become a hot debate in Indonesia. This study examines the constitutional legitimacy of the regional head election system through the DPRD within the framework of the Indonesian constitutional system. The 1945 Constitution of the Republic of Indonesia Article 18 paragraph (4) states that regional heads are "democratically elected", which provides a wide interpretation of the election mechanism, either directly or indirectly through representatives. This change in the election mechanism is not just a technical administrative issue, but has profound legal implications for the constitutional structure, democratic legitimacy, and the local government system as a whole. In constitutional law theories such as the principles of democracy, people's sovereignty, and regional autonomy, the election of regional heads through the DPRD creates different legal dynamics compared to the direct election system, both in the context of the power relationship between the executive and the regional legislature and in terms of political accountability to the community. This research uses a normative juridical method with a qualitative approach, which is carried out by examining laws and regulations, legal doctrines, and court decisions related to the election of regional heads through the DPRD. The results of the study show that the election system through the DPRD has constitutional legitimacy, but it carries legal consequences in the form of changes in the power structure, transformation of people's sovereignty from direct to indirect, and the potential for increased transactional politics.